Viral mHealth​ - Stefan Fölster (Taylor & Francis Group, 2017)
Thousands of mHealth applications are developed every year, but few of these spread or 'go viral'. Even clinical applications that provide health benefits and social value often linger after an initial pilot phase. An examination of common hindrances in low-income countries suggests that more subsidies and education of health care personnel are insufficient solutions. Instead we propose better a priori screening of mHealth applications based on four criteria that may largely determine whether an mHealth application will spread. Further, we illustrate how using these criteria forms a good basis for involving 'impact investors' in the development of mHealth applications. This can reduce risks for public health care providers and increase the likelihood of success.